The Karkheh River Basin: the food basket of Iran under pressure. - Ahmad, M.D.; Giordano, Mark (Routledge, 2012)
Two strategies are assessed to increase wheat production in the water-scarce Karkheh River Basin (KRB) in Iran to meet targets by the year 2025. The strategies proposed are (a) to increase yields in the current irrigated and rainfed wheat areas and (b) to increase the area under rainfed wheat through land conversion. Crop water consumption, based on satellite remote sensing and crop yield data, was used to estimate crop water productivity (CWP) in irrigated and rainfed wheat areas in five sub-basins. CWP for wheat ranges from 0.51.63 kg m-3 in irrigated areas to 0.370.62 kg m-3 in rainfed areas. Conditions indicating water-stress in wheat areas were assessed by relative evapotranspiration (ETa/ETp) and showed that water-stress only had a minimal effect for about 154,000 ha of irrigated wheat (57%). Land suitability analysis showed that about 71,000 ha of rangelands can be converted into rainfed wheat areas without harming the current water balance in the basin. Statistical analyses showed that more than 70% of the variation in irrigated and rainfed wheat yield at plot level can be explained by water, fertilizer and seed rates. This suggests that wheat production can be increased by improving inputs other than water. Results from this study indicate that it is possible to meet approximately 85% of the wheat production targets in the year 2025 when strategies are combined.